India-Us relations in the Modi era - Edited by Pant, Harsh V (New Delhi Har-Anand Publications, 2024)
INDIA-US RELAIONS IN THE MODI ERA As one of the most significant bilateral relationships, the India-US partnership has strengthened notably under the leadership of Prime Minister Narendra Modi. Factors such as managing China$1 (Bs increasing presence in the Indo-Pacific, shared commitment to democratic values, alignment on trade and advanced technology, the imperative of environmental sustainability, and cooperation on non-traditional security issues have deepened this alliance. The establishment of institutional mechanisms has led to a maturing of this bilateral relationship, allowing the two to more effectively overcome political hurdles. The book provides a comprehensive overview of India's interactions with successive US administrations under PM Modi, encompassing trade, technology collaboration, defence ties, the Indo-Pacific region, and counterterrorism efforts. It is valuable for both foreign policy specialists and general readers, offering insights into an uncertain era characterized by geopolitical shifts and power transitions. ABOUT THE AUTHORS Harsh V Pant is Vice President for Studies and Foreign Policy at Observer Research Foundation, New Delhi. He is a Professor of International Relations with King$1 (Bs India Institute at King$1 (Bs College London. He is also Director (Honorary) of Delhi School of Transnational Affairs at Delhi University. Professor Pant$1 (Bs current research is focused on Asian security issues. Vivek Lall is the Chief Executive of General Atomics Global Corporation. Earlier, he has been associated with Boeing, Lockheed Martin, and Raytheon. Mr Lall was also affiliated with the United Nations as an adviser on broadband and cyber security issues. A Visiting Distinguished Fellow at the Observer Research Foundation, he has served as the chairman of the Indo-US Strategic Dialogue, hosted by the Indo-American Chamber of Commerce. He holds a Ph.D. in Aerospace Engineering from Wichita State University, United States.s
Keywords: Prime Minister; Narendra Modi; Indian Foreign Policy